Advance Care Planning Initiatives in Critical Care Centers in Japan: A Case Report - Yuni Kamimura; Michihiro Tsubaki; Jun Hattori; Marina Oi; Takaaki Maruhashi; Haruyo Ota; Miho Oki; Kota Takanashi; Maika Takahashi; Yoko Sakurai; Yasushi Asari (Clinical Case Reports)
ABSTRACT This report examines the promotion of advance care planning (ACP) for patients admitted to critical care centers and discharged to home. Emergency transport experience allows patients and their families to realistically discuss her ACP.